Diversity and distribution of benthic macroinvertebrates in Krueng Aceh watershed, Aceh Province, Indonesia - CHITRA OCTAVINA; ZAINAL A. MUCHLISIN; PURWANA SATRIYO; AMIRAH HURZAID (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Octavina C, Muchlisin ZA, Satriyo P, Hurzaid A. 2025. Diversity and distribution of benthic macroinvertebrates in Krueng Aceh watershed, Aceh Province, Indonesia. Biodiversitas 26: 601-616. Krueng Aceh, the densest watershed in Aceh Province, Indonesia, features diverse habitats with rainwater as its main source. However, agriculture, plantations, sand mining, and waste disposal have affected its aesthetics. This study examines the diversity and distribution of benthic macroinvertebrates in Krueng Aceh. Conducted over six months (March-August 2024), it used purposive sampling at 10 stations (upstream, midstream, and downstream). Surber nets sampled upstream and midstream, while PVC pipes were used downstream. A total of 1240 benthic macroinvertebrates were identified across 3 phyla, 5 classes, 29 families, 42 genera, and 49 species. Hydropsyche angustipennis dominated hard substrates, while Tarebia granifera dominated soft substrates. Most macroinvertebrates exhibited a clustered distribution, with some showing no clear pattern. The diversity index (H') ranged from 0.99 to 3.46 (moderate to high), and the Simpson dominance index from 0.10 to 0.62 (low dominance). Hierarchical Cluster Analysis (HCA) grouped the 10 stations into two similarity clusters. Overall, macroinvertebrate diversity in Krueng Aceh was relatively high, and water quality remained within acceptable standards.